2016
DOI: 10.1590/1806-9282.62.05.407
|View full text |Cite
|
Sign up to set email alerts
|

Disease-free survival in patients with non-metastatic breast cancer

Abstract: Introduction: Breast cancer is the second most common malignancy in the world and the one with highest incidence in the female population; it is also a major cause of death from cancer among women. Objective: To analyze the disease-free survival (DFS) at 5 years and prognostic factors in women with non-metastatic invasive breast cancer treated at a referral center for cancer care located in a medium-sized city in the Southeast of Brazil. Method: Patients diagnosed with the disease between 2003 and 2005 and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
1
7
0
2
Order By: Relevance
“…Klotho is a protein that is considered to be closely tied to lifespan; therefore, investigating the overall lifespan of patients was of interest. There was no difference in overall patient survival depending on αKlotho status, but results similar to those encountered in the literature were obtained when considering certain variables, such as molecular subtype, tumor grade, lymph node status and TNM classification (78)(79)(80)(81). The present results demonstrated that patients with tumors that had certain histopathological variables considered important for overall survival had undetected αKlotho.…”
Section: Multivariate Analysis a -supporting
confidence: 89%
“…Klotho is a protein that is considered to be closely tied to lifespan; therefore, investigating the overall lifespan of patients was of interest. There was no difference in overall patient survival depending on αKlotho status, but results similar to those encountered in the literature were obtained when considering certain variables, such as molecular subtype, tumor grade, lymph node status and TNM classification (78)(79)(80)(81). The present results demonstrated that patients with tumors that had certain histopathological variables considered important for overall survival had undetected αKlotho.…”
Section: Multivariate Analysis a -supporting
confidence: 89%
“…Overall 5-year disease-free rates: ipsilateral breast tumour recurrence,97.4%; LR,95.6%; DM: 92.9%, and cancer–specific death:96.3%. Significant difference in survival between subtypes (of invasive breast cancer) for LR, DM and breast cancer–specific death Diniz et al 2016, Brazil (South America) [ 11 ] Disease-free survival in patients with NMBC Three-year retrospective single-centre study:563 cases Disease recurrence noted in 129 cases:17.8% LR; 54.3% DM and 27.9% died. Disease free survival at 5 years:72% Budakoglu et al 2014, Turkey (Eurasia) [ 12 ] Outcome of triple negative NMBC patients Eleven-year multi-center retrospective study:561 cases Ratio of triple-negative breast cancer:12%.…”
Section: Resultsmentioning
confidence: 99%
“…O estudo dessa variável permite ainda realizar comparações, como busca precoce por diagnóstico, adesão ao tratamento, avaliação de sobrevida e recidiva da doença, entre outras. Várias pesquisas foram realizadas na busca de analisar os fatores associados à escolaridade e ao câncer de mama [24][25][26] . Esses estudos apontam que, talvez por causa do estilo de vida e comportamento, o resultado das mulheres com escolaridade maior foi melhor que das demais.…”
Section: Discussionunclassified
“…Pesquisas realizadas com dados do RHC do Brasil e de Minas Gerais observaram grau de completitude "regular" para a variável estado da doença ao final do primeiro tratamento. Vários estudos foram realizados 25,[38][39][40][41][42] com o objetivo de analisar diferentes tipos de tratamento. Para comparar os procedimentos realizados na assistência oncológica, informações acerca do tratamento precisam estar registradas no prontuário.…”
Section: Discussionunclassified